Atomically-thin single-photon sources for quantum communication - Timm Gao; Martin von Helversen; Carlos Antón-Solanas; Christian Schneider; Tobias Heindel (npj 2D Materials and Applications, 2023)
Abstract To date, quantum communication widely relies on attenuated lasers for secret key generation. In future quantum networks, fundamental limitations resulting from their probabilistic photon distribution must be overcome by using deterministic quantum light sources. Confined excitons in monolayers of transition metal dichalcogenides (TMDCs) constitute an emerging type of emitter for quantum light generation. These atomically thin solid-state sources show appealing prospects for large-scale and low-cost device integration, meeting the demands of quantum information technologies. Here, we pioneer the practical suitability of TMDC devices in quantum communication. We employ a WSe2 monolayer single-photon source to emulate the BB84 protocol in a quantum key distribution (QKD) setup and achieve click rates of up to 66.95 kHz and antibunching values down to 0.034—a performance competitive with QKD experiments using semiconductor quantum dots or color centers in diamond. Our work opens the route towards wider applications of quantum information technologies using TMDC single-photon sources.